Evaluation of Human β-defensin-3 Diagnostic Role in a Group of Iraqi Patients with Osteoporosis - Hassan, Zahraa S.; Farhan, Layla O. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Osteoporosis (OP) is a prevalent age-related condition that increases the risk of fracture and bone fragility, as result loss of bone mass as well as micro-architectural degradation of the bone, thereby reducing the mass and strength of bone. Human β-defensin (HBD-3) is ananti-inflammatory peptide andcrucial part of the human innate immune system. Giving early therapeutic intervention for OP requires an early diagnosis. Objectives: To evaluate the serum HBD-3 accuracy of diagnosis in patients with osteoporosis. Methods: The study was conducted in the National Joint Center at Yarmouk Teaching Hospital in Baghdad during September - October 2023. Eighty participants were recruited, all of whom had clinical examinations and had their bone status measured by dual-energy X-ray absorptiometry (DXA). Levels of serum HBD-3 and vitamin D3 (Vit D3) were determined by the ELISA technique. Calcium level (Ca+2) was measured using a spectrophotometer. A comparative study was conducted between forty patients with OP and 40 controls. The study included females and males with an age range between (40-60) years. Results: The serum level of HBD-3 in the OP group was significantly higher (p < 0.001) than that of the healthy controls. The area under the curve (AUC) was found to be (1.000) in the ROC curve analysis for serum HBD-3 level. Conclusion: Serum HBD-3 can be a valuable indicator of OP in middle-aged individuals, and may be a helpful biological marker for OP diagnosis.